The Effectiveness Of The Regional Head Election (Pilkada) Implementation In Bengkulu City - Lorita, Evi; Sariningsih, Marida; Sintia, Nopa (Journal of Research in Social Science and Humanities, 2021)
This study aims to analyze the effectiveness of the performance of the Secretariat staff of the Bengkulu City General Election Commission (KPU) in the implementation of the 2018 Regional Head Election (Pilkada). A descriptive qualitative method was used, with data collected through in-depth interviews, observations, and documentation. The research focused on five effectiveness indicators according to Hasibuan: job performance, responsibility, discipline, honesty, and teamwork. The findings indicate that KPU Secretariat staff carried out their duties in alignment with these indicators, although several technical challenges were encountered. The election schedule was implemented according to the planned timeline, and inter-staff cooperation was notably high. Therefore, the staff's performance is categorized as effective and contributed significantly to the successful execution of the Pilkada in Bengkulu City. This study contributes to a deeper understanding of the importance of professionalism and accountability among election administrators as a foundation for local democratic governance.